Remoção de coliformes e Ascaris lumbricoides em sistema de wetland construído de fluxo vertical - Trevisan, Gabriel de Menezes (2017)
According to WHO (WHO, 2011), about 1.8 million people die from intestinal gastro diseases, mostly caused by viruses, bacteria, protozoa and helminths. This work aimed to evaluate the removal of coliforms and Ascaris lumbricoides in a decentralized system of treatment of domestic effluents, consisting of septic tank followed by wetland constructed of vertical flow. This study was carried out at the experimental effluent treatment system (ETS) implanted at the Federal University of Santa Maria (UFSM). The ETS was designed and implemented to treat a portion of the effluent generated by the University Student House II - CEU II, 1,500 L / d, equivalent to 10 people. The quantification of total coliforms and E. coli followed the methodology of the Enzymatic Substrate (9223 B. 2. b.). The presence and quantification analyze of helminth and cysts eggs followed the method described in Appendix I of the Control of Pathogens and Vector Attractions in Sewage Sludge. Eighty - six samples of effluents were collected. The removal of total coliforms occurred in the WCFV were 0.23 log and 0.25 log for E. coli. The TS removals were 0.37 Log for total coliforms and 0.35 Log for E. coli. The total removal of total coliforms and E. coli was 0.60 log units. Helminth eggs were found in 5 of the 15 samples, evidencing the absence or very low incidence of these parasites in the UFSM CEU II population, where TS removal was approximately 61.3% and WC 100%. The comparison of operational phases of the system showed the negative influence of the recirculation when analyzed the removal of total coliforms in TS, already for the removal of E. coli even had no significant influence. The TAH, the macrophyte used and the temperature were the contour conditions that most influenced WC removal. Disinfection showed good inactivation of coliforms and E. coli (2.11 and 2.5 respectively) even with residual chlorine residual. The treatment system as a whole showed good results in the removal of helminth eggs, but to achieve the release standards in water bodies with respect to total coliforms and E. coli, a disinfection step is necessary